Hydroalcoholic and polyphenolic extracts of Ziziphus Jujuba Mill fruits prevent methyl methanesulfonate-induced DNA damage in HepG2 cells - Mahmoud Etebari; Behzad Zolfaghari; Abbas Jafarian-Dehkordi; Afsaneh Mirzaei (Mazandaran University of Medical Sciences, 2015)
Ziziphus jujuba Mill (ZJ), which has been extensively used by the Iranian traditional healers, belongs to the Ramnaceae family. This semitropical herb contains large quantities of polyphenols and flavonoids, which in turn reveal antioxidant, antibacterial, free radical scavengering, and several other pharmacological activities. The purpose of the present study was to evaluate the DNA damage prevention potential of hydroalcoholic and polyphenolic extracts of Ziziphus jujuba on HepG2 cells. Throughout the assessment of genoprotective properties, cells were incubated with various concentrations of hydroalcoholic (0.1, 1, 10, and 50 µg/ml) and polyphenolic extracts (0.1 and 1 µg/ml) for a one-hour period, followed by a one-hour incubation period with genotoxic concentration of methyl methanesulfonate (MMS) (10 µM). The comet assay method was applied because of its being attributable to the substantial sensitivity, its inexpensiveness, and its straightforward procedure of use. The tail length, percentage of DNA in tail, and tail moment were measured. Statistical analysis revealed that concentrations of 10 μg/ml for hydroalcoholic extract and 1μg/ml for polyphenolic extract were genoprotective against MMS. Therefore, our results suggest that Ziziphus jujuba at suitable doses can prevent DNA damage.